Performance and dynamics of active greywater heat recovery in buildings. (1st January 2022) - Hadengue, Bruno; Morgenroth, Eberhard; Larsen, Tove A.; Baldini, Luca
Highlights: We investigate active greywater heat recovery with heat pumps under various conditions. Colder climates and large hot water consumption induce larger electricity savings. We identify and compare various system configurations for heat recovery. Closed-loop systems, with greywater as direct heat source, show largest potential. Abstract: In the effort to de-carbonize the building stock, heat pumps are increasingly utilized in Switzerland, with 70% of the fast-growing heat pump market using ambient air as heat source. Inexpensive and easy to implement, these heat pumps are, however, less efficient than their ground- or water-source counterparts. In this modeling study, we aim at increasing the efficiency of air-source heat pumps using domestic greywater-contained heat. We assess the performance improvement relative to standard heat pump configurations across various climates, seasons, building envelopes, and domestic hot water consumption patterns. The results show that the annually-averaged coefficient of performance improves by 4.1% on average – ranging from 0.6% to 7.5%. This efficiency gain translates on average to 1.8 kWh/week of compressor electricity savings. Although attractive due to its simplicity, the proposed open-loop configuration – preheating of an external heat source – only leads to moderate performance improvement of air-source heat pumps. Based on these results, we extensively discuss and compare alternative system configurations and identify several fundamental differences in the heat recovery dynamics of each configuration. We show that closed-loop systems – using greywater as direct heat source – show the largest performance improvement potential, although being more expensive and complex to implement.